Understanding Lung Abscess: Clinical Manifestations, Diagnosis, and Management - Hadinata, Lalu Gde Gilang Alid; Angelita, Puja Rizkina; Lativa, Nindy Citra; Ningsih, Nur Aulia Ahya (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Lung abscess is a pulmonary condition characterized by a localized collection of pus within lung tissue, usually caused by bacterial infection. It often occurs as a complication of pneumonia, aspiration, or in individuals with weakened immune systems. This literature review aims to discuss the definition, etiology, epidemiology, clinical manifestations, diagnosis, management, and prognosis of lung abscess to provide a better understanding of this disease and its optimal treatment approach. The review was conducted based on recent literature and clinical guidelines related to lung abscess, including national and international sources such as the Indonesian Society of Pulmonologists (PDPI), WHO reports, and recent journal publications. Lung abscess is primarily caused by anaerobic bacteria and Staphylococcus aureus. The main clinical features include fever, productive cough with foul-smelling sputum, chest pain, and shortness of breath. Diagnosis is established through clinical examination, sputum analysis, and radiological imaging such as chest X-ray or CT scan. The main treatment involves antibiotic therapy, followed by drainage or surgical procedures if no improvement occurs. Prognosis depends on early diagnosis and appropriate antibiotic use, with mortality rates ranging from 10–20%. Early recognition and proper management of lung abscess are essential to prevent complications such as empyema or bronchopleural fistula. Rational antibiotic use and supportive care remain the cornerstone of therapy, while surgical intervention is reserved for refractory cases.